Pelatihan Penggunaan Sistem Informasi Keuangan Sekolah Muhammadiyah (SIKeSMu) Pada Majelis Pendidikan Dasar dan Menengah Muhammadiyah Kota Medan - Surya Darma Nasution; Suginam Suginam; Mesran Mesran (Journal of Social Responsibility Projects by Higher Education Forum, 2021)
The Medan City Muhammadiyah Elementary and Secondary Education Council is an institution or organization whose activities are related to religion. One of the activities of the Medan City Muhammadiyah Elementary and Secondary Education Council is to supervise reporting and carry out Monitoring and Evaluation (Monev) of financial reports from Muhammadiyah schools that are members of the assembly so that financial problems in these schools become transparent. Based on the analysis of the situation of the target audience that has been stated above, the problems faced so far have occurred in two directions, where the assembly and the school both have problems in monitoring and evaluating the financial statements so that the right solution is needed to resolve both the problem. The solution to the existing problems is to build the Muhammadiyah School Financial Information System Application (SIKeSMu) and provide training for the use of the application so that it is hoped that later it can simplify reporting and facilitate monitoring of financial statements in schools that are members of the Primary and Secondary Education Council. Muhammadiyah Medan City.